Implementing outcome-based education (obe): are we ready and willing? - Ariffin, Kamisah; Alias, Asmidar; Mohd Bhkari, Norshariza; Khalid, Khairi (Universiti Teknologi MARA, 2009)
Outcome-Based Education (OBE) is now making its way into our tertiary education system through the accreditation regulatory under the Malaysian Qualification Agency (MQA) Act 2007. The main reason for the implementation of OBE is to ensure that accreditation practices in this country meet the practices of the international accreditation accords. However, this has raised the issue whether or not the spirit of the transformation will be willingly shared and the concept of OBE will be readily embraced by all involved. This paper reports the current situation of the lecturers' readiness and willingness to embrace the concept and implement OBE in the classroom.